My Hermitage - Piotrovskij, Michail Borisovič 1944- (Skira Rizzoli, 2015)
In a memoir, the museum's longtime director takes the reader on a private tour of this global treasure. Holding one of the largest collections of Western art in the world, the Hermitage is also a product of Russia and its dramatic history. Founded by Empress Catherine the Great in 1764, the stunning Winter Palace was built to house her growing collection of Old Masters and to serve as a home for the imperial family. Tsars came and went over the years, artworks were acquired and sold, buildings were burned down in terrible fires, and still the collections grew. After the violent upheavals of the Russian Revolution in 1917, the palaces and collections were opened to the public. Now, in an unprecedented collection of illuminating essays, Piotrovsky explores the cultural history of a collection as rich in adventure as art. From fascinating intrigues to revelatory scholarship on the collection's incredible art and artifacts, My Hermitage is a profound and captivating story of art's timelessness and how it brings people together.